(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. The synergy of central and peripheral changes while performing easy exercises in repetitive manner should show central or peripheral changes which start increasing and become a trigger for functional mobilization. Research aim. The aim of this study was to determine the mobilization peculiarities of central and peripheral cardiovascular function in Greco-Roman wrestlers cohort while performing a dosed exercise test in repetitive manner. Research methods. Greco-Roman wrestlers, sprinters, endurance runners and non-athletes underwent three Roufier tests (30 squats per 45s) with 2 minutes of recovery between them. The changes in the heart rate (HR) and JT interval taken from 12-lead ECG and O 2 desaturation (StO 2 ) registered by near-infrared spectroscopy were analyzed. Research results. HR increased and JT interval decreased more and more in both non-athlete cohorts while there were no significant changes in all three athlete cohorts, i. e. we did not find any summing effects of the repetition of workloads. The tendency of increase in StO 2 at the second minute after the dosed workload was greater and greater with each consequent repetition of the testing workload in all cohorts. Discussion and conclusions. We have proved our hypothesis that peripheral changes during repetitive exercising start increasing earlier than the central ones. The dynamics of central and peripheral cardiovascular indices in non- athlete cohorts while repeating a dosed aerobic exercise test every two minutes demonstrates the cumulative effect of physical exertion whereas in elite Greco-Roman wrestlers as well as in other individuals adapted to physical loads functional indices reiterated. Keywords: electrocardiogram, dosed exercise test, oxygen saturation.